A Review on Assessment Quality of Fruits using Non-destructive Method - Kok, Win Leong; Ong, Pauline (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Ensuring the quality of fruits will increase its productivity and marketability. However, predicting the fruit quality from human experiences is not reliable and cannot guarantee the quality of fruits because the fruit properties change rapidly during the fruit ripening process and the fruit development. Many instruments can be used to measure the total soluble solid of fruits, but mostly are destructive methods. In this paper, several rapid and non-destructive methods to determine the quality of fruits were reviewed. The result of each type of method and the obtained accuracy were presented.